Digest it all: the lysosomal turnover of cytoplasmic aggregates. Issue 3 (March 2023) - Mauthe, Mario; Kampinga, Harm H.; Hipp, Mark S.; Reggiori, Fulvio
Abstract: Aggrephagy describes the selective lysosomal transport and turnover of cytoplasmic protein aggregates by macro-autophagy. In this process, protein aggregates and conglomerates are polyubiquitinated and then sequestered by autophagosomes. Soluble selective autophagy receptors (SARs) are central to aggrephagy and physically bind to both ubiquitin and the autophagy machinery, thus linking the cargo to the forming autophagosomal membrane. Because the accumulation of protein aggregates is associated with cytotoxicity in several diseases, a better molecular understanding of aggrephagy might provide a conceptual framework to develop therapeutic strategies aimed at delaying the onset of these pathologies by preventing the buildup of potentially toxic aggregates. We review recent advances in our knowledge about the mechanism of aggrephagy. Highlights: Macro-autophagy in general, and selective autophagy receptors (SARs) in particular, are central players of the cellular protein quality control (QC) system that maintains protein homeostasis through the removal of aggregates. Aggrephagy substrates are generically termed aggregates. Although the term specifically refers to the association of two or more protein molecules in a non-functional state, aggrephagy substrates also include a variety of conglomerates with different biophysical and/or structural features that do not always match the general definition of an aggregate. Recent evidence demonstrates that cells have evolved a multilayered mechanism to ensure the degradation of cytoplasmic aggregates and conglomerates by developing partial redundancies in the mechanism of aggregate recognition in a single aggrephagy pathway, among aggrephagy pathways, and among different degradation systems. The removal of aggregates by aggrephagy can be disturbed when other aspects of protein QC, including chaperone-mediated autophagy (CMA), are impaired.